Two new species of Heteropterna Skuse, 1888 (Diptera: Keroplatidae) from China - Wang, Qingyun; Qi, Lei; Wu, Hong; Huang, Junhao (Zootaxa, 2021)
Two new species of Heteroptera (Diptera: Keroplatidae: Keroplatinae), H. cuneata sp. n. and H. fanjingshana sp. n. are described from Guizhou, China. Key to adult males of Heteropterna from China is given. Habitus images of adults and morphological structures are provided.